2015
DOI: 10.1152/physiolgenomics.00110.2014
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet caused widespread epigenomic differences on hepatic methylome in rat

Abstract: Pan YX. High-fat diet caused widespread epigenomic differences on hepatic methylome in rat. Physiol Genomics 47: 514 -523, 2015. First published July 21, 2015; doi:10.1152/physiolgenomics.00110.2014.-A high-fat (HF) diet is associated with progression of liver diseases. To illustrate genome-wide landscape of DNA methylation in liver of rats fed either a control or HF diet, two enrichment-based methods, namely methyl-DNA immunoprecipitation assay with high-throughput sequencing (MeDIP-seq) and methylation-sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 36 publications
4
24
0
Order By: Relevance
“…It is concurrent with previous findings that HFD causes changes in methylation status of specific genes involved in glucose and lipid metabolism of liver, inflammation, and liver development [1011121327]. In a previous study that investigated the genome-wide effect of HFD on liver DNA methylation starting from mouse conception, annotated genes with DMRs were enriched in signaling pathways of liver steatosis and liver development such as cell morphogenesis, developmental growth, response to stimuli, signal transduction, and triacylglycerol biosynthesis [14]. Therefore, results from this study could complement current knowledge by providing genome-wide evidence that HFD affects biological networks associated with liver lipid accumulation and liver diseases even during the adulthood.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…It is concurrent with previous findings that HFD causes changes in methylation status of specific genes involved in glucose and lipid metabolism of liver, inflammation, and liver development [1011121327]. In a previous study that investigated the genome-wide effect of HFD on liver DNA methylation starting from mouse conception, annotated genes with DMRs were enriched in signaling pathways of liver steatosis and liver development such as cell morphogenesis, developmental growth, response to stimuli, signal transduction, and triacylglycerol biosynthesis [14]. Therefore, results from this study could complement current knowledge by providing genome-wide evidence that HFD affects biological networks associated with liver lipid accumulation and liver diseases even during the adulthood.…”
Section: Discussionsupporting
confidence: 82%
“…There was a similar high-throughput approach previously, in which the effect of HFD was examined from mouse conception through the adulthood [14]. The current study differs in its design from the previous study in that it examined the effect of HFD consumption during the adulthood only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that folate depletion during pregnancy evoked approximately three times more changes in expression than in DNA methylation (expression of 989 genes v. methylation of 333 gene promoters) in the fetal liver . Others have reported genome‐wide, but also relatively small, changes in DNA methylation in the liver of rat offspring from dams fed a high‐fat diet (45% of energy from fat) throughout gestation and lactation and to the offspring from weaning until 12 weeks of age .…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported genome-wide, but also relatively small, changes in DNA methylation in the liver of rat offspring from dams fed a high-fat diet (45% of energy from fat) throughout gestation and lactation and to the offspring from weaning until 12 weeks of age [68]. Whilst we observed simultaneous changes in gene expression and promoter DNA methylation in response to both nutritional exposures investigated, we found no significant overlap between gene lists for which expression and promoter methylation were altered in response to a given exposure.…”
Section: Maternal Folate Depletion and Post-weaning High Fat Intake Amentioning
confidence: 99%